Economic evaluation of a randomized controlled trial of an intervention to reduce office workers' sitting time: the "Stand Up Victoria" trial - Lan Gao; Anna Flego; David W Dunstan; Elisabeth AH Winkler; Genevieve N Healy; Elizabeth G Eakin; Lisa Willenberg; Neville Owen; Anthony D LaMontagne; Anita Lal; Glen H Wiesner; Nyssa T Hadgraft; et al. (Nordic Association of Occupational Safety and Health (NOROSH), 2018)
OBJECTIVES: This study aimed to assess the economic credentials of a workplace-delivered intervention to reduce sitting time among desk-based workers. METHODS: We performed within-trial cost-efficacy analysis and long-term cost-effectiveness analysis (CEA) and recruited 231 desk-based workers, aged 24-65 years, across 14 worksites of one organization. Multicomponent workplace-delivered intervention was compared to usual practice. Main outcome measures including total device-measured workplace sitting time, body mass index (BMI), self-reported health-related quality of life (Assessment of Quality of Life-8D, AQoL-8D), and absenteeism measured at 12 months. RESULTS: Compared to usual practice, the intervention was associated with greater cost (AU$431/person), benefits in terms of reduced workplace sitting time [-46.8 minutes/8-hour workday, 95% confidence interval (CI): -69.9- -23.7] and increased workplace standing time (42.2 minutes/8-hour workday, 95% CI 23.8-60.6). However, there were no significant benefits for BMI [0.148 kg/m^2 (95% CI-1.407-1.703)], QoL-8D [-0.006 (95% CI -0.074-0.063)] and absenteeism [2.12 days (95% CI -2.01-6.26)]. The incremental cost-efficacy ratios (ICER) ranged from AU$9.94 cost/minute reduction in workplace sitting time to AU$13.37/minute reduction in overall sitting time. CEA showed the intervention contributed to higher life year (LY) gains [0.01 (95% CI 0.009-0.011)], higher health-adjusted life year (HALY) gains [0.012 (95% CI 0.0105 - 0.0135)], and higher net costs [AU$344 (95% CI $331-358)], with corresponding ICER of AU$34 443/LY and AU$28 703/HALY if the intervention effects were to be sustained for five-years. CEA results were sensitive to assumptions surrounding intervention-effect decay rate and discount rate. CONCLUSIONS: The intervention was cost-effective over the lifetime of the cohort when scaled up to the national workforce and provides important